Shifts in Pattern of Specialization: Case Studies of India and China - Tri Widodo (Gadjah Mada International Journal of Business, 2008)
This paper examines shifts in pattern of specialization of China’s and India’s exported groups of products defined in the three-digit Standard International Trade Classification (SITC) Revision 2. This paper applies Revealed Symmetric Comparative Advantages (RSCA) index and Spearman’s rank correlation. Some conclusions are withdrawn. First, on average the comparative advantages of both China and India increase, except in the case of China for the period of 1998-2003. Second, China’s pattern of comparative advantage changes more dynamically than that of India. Third, the China’s and India’s patterns of comparative advantage show different trends (divergent/more complementary).